Does improved accessibility translate into tourism growth? A difference-in-differences analysis of bridge infrastructure in Indonesia - Wahyu Wisnu Wardana; Tri Haryanto; Iqram Ramadhan Jamil; Nor Asmat Ismail; Unggul Heriqbaldi; Ebou Correa; Wiwit Nur Rohmah; Shochrul Rohmatul Ajija (Annals of Tourism Research Empirical Insights, 2025)
Tourism growth relies heavily on transport infrastructure. In regions with unique geography, enhanced accessibility can significantly boost tourism. This study examines the impact of the Suramadu Bridge on tourism on Madura Island, Indonesia, using a difference-in-difference (DiD) approach. Unlike prior research focusing on rail transport, this study highlights the overlooked role of bridges in regional tourism. Findings reveal that, unexpectedly, the bridge did not significantly boost tourism, aligning with Leiper's open system framework. Despite the enhanced accessibility, internal barriers to tourism remain. The study highlights the need for integrated planning, multi-stakeholder strategies, and complementary policies to maximize infrastructure benefits. It also emphasizes the importance of viability studies to guide future projects.